Virtue in Political Life : Yves Simons Political Philosophy for Our Times - Lafon, Patrick (Book collections on Project MUSE., 2018)
Yves R. Simon (1903-1961), one of the greatest contemporary philosophers, gives a modern formulation for many classical philosophical concepts such as authority, the common good, and natural law. These topics have received extensive attention from scholars. Simon also discusses the nature of human virtue, moral and intellectual, but this topic has been less studied until now. The idea of virtue, and in our case virtue in political life, runs through Simon's works. Through a close study of Simon's works and the relevant secondary literature, this book explores Simon's definition of virtue in order to highlight its originality, and show how he weaves the need for it into the fabric of three facets of political life, namely, the common good, the virtue of the ruler and the ruled, and the law. These ideas are important for the ruler-ship of any country and especially of developing nations which are populated by sit-tight dictators. Philosophy can be dry and abstract, yet in this case we deal with one of its more practical manifestations.